A Comparative Review of Takaful Frameworks in Nigeria, Malaysia and Pakistan - Dikko, Maryam; Abu Bakar, Mahyuddin (UUM Press, 2018)
This paper was undertaken with the purpose of conducting a critical review of the framework for Takaful in Nigeria in achieving shariah compliance by comparing it with those available in Malaysia and Pakistan. The review looked at laws and other regulations, Takaful operations including models and marketing structure and dispute resolution mechanisms. The study found there are loopholes within the Nigerian system as compared to those in Malaysia and Pakistan regarding enacted legislation and requirements for capacity to serve on shariah advisory boards. Deficiencies also exist with regard to the qualification requirements for management and marketing staff and in the absence of an adequate dispute resolution mechanism. Recommendations arising from the research include suggestion that Nigeria enact specific all-encompassing legislation to regulate Takaful. There is also the need for the creation of a specialized system for resolving Takaful disputes and the requirement of specialized training for Takaful personnel.